Work disability in non-radiographic axial spondyloarthritis patients before and after start of anti-TNF therapy: a population-based regional cohort study from southern Sweden. (7th January 2017) - Wallman, Johan K.; Jöud, Anna; Olofsson, Tor; Jacobsson, Lennart T. H.; Bliddal, Henning; Kristensen, Lars E.
Abstract: Objective. The aim was to assess work-loss days before and after commencement of anti-TNF treatment in patients with non-radiographic axial spondylarthritis (nr-axSpA). Methods. Bionaïve nr-axSpA patients (n = 75), aged 17–62 years, fulfilling the Assessment of SpondyloArthritis international Society criteria for axial spondyloarthritis and starting anti-TNF treatment during 2004–11, were retrieved from the observational South Swedish Arthritis Treatment Group study. Patient information was linked to Swedish Social Insurance Agency data on sick leave and disability pension from 1 year before to 2 years after anti-TNF initiation. Matched population references were included for comparison and to adjust for secular trends. Results. The nr-axSpA patients had a median age of 35 years and disease duration of 6 years at the start of treatment. During the 2 years after anti-TNF initiation, mean work-loss days (including both sick leave and disability pension) in the nr-axSpA group decreased significantly from 3.4 to 1.9 times more than among the population references. The effect was seen on sick leave, whereas disability pension levels remained similar in both groups throughout. Conclusion. Anti-TNF therapy in nr-axSpA was associated with a significant and sustained improvement of work disability over 2 years. However, the proportion of work-loss days remained almost twice as high as in the general population at the end of follow-up.